EARNINGS MANAGEMENT: A LITERATURE REVIEW - Debbianita Debbianita; Tan Ming Kuang; Marcella Hoetama (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2024)
Earning is an important component in financial statements that can be modified by management policies. Managers have the opportunity to present profits according to their wishes because managers have more information so they are free to do this which is called earnings management. In our study, the researchers attempt to review the literature studies that provide an analysis of earnings management impact from two perspectives. The researcher attempts to review existing research/literatures that provide an analysis of earnings management from two perspectives. The articles used in this study consist of 50 articles on earnings management that have been published in international journals and were obtained from Google Scholar using the keyword "earnings management". The research findings indicate that the majority of the articles are quantitative studies utilizing the accrual-based earnings management approach and possess an opportunistic perspective towards earnings management. Research on earnings management has been extensively conducted, but only a few have explored earnings management from a signal perspective. The study aims to examine two different point of view from earnings management article.